2022
DOI: 10.1002/osp4.598
|View full text |Cite
|
Sign up to set email alerts
|

Beer, wine, and spirits differentially influence body composition in older white adults–a United Kingdom Biobank study

Abstract: BACKGROUND:Aging is characterized by body composition alterations, including increased visceral adiposity accumulation and bone loss. Alcohol consumption may partially drive these alterations, but findings are mixed. This study primarily aimed to investigate whether different alcohol types (beer/cider, red wine, white wine/ Champagne, spirits) differentially associated with body composition. METHODS:The longitudinal UK Biobank study leveraged 1869 White participants (40-80 years; 59% male). Participants self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Moreover, there is a considerable interest to discriminate between the different alcoholic beverages: that is, to objectively assess the type of alcoholic beverage consumed. For instance, physiological or health effects specifically related to red wine or beer have recently been reviewed [ 13 15 ]. Assessing compliance is also important and demands objective tools to assess alcohol consumption; factors such as the time lapse since the last drink, the frequency of drinking, and the different beverages consumed are also important questions in need of objective biomarker strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is a considerable interest to discriminate between the different alcoholic beverages: that is, to objectively assess the type of alcoholic beverage consumed. For instance, physiological or health effects specifically related to red wine or beer have recently been reviewed [ 13 15 ]. Assessing compliance is also important and demands objective tools to assess alcohol consumption; factors such as the time lapse since the last drink, the frequency of drinking, and the different beverages consumed are also important questions in need of objective biomarker strategies.…”
Section: Introductionmentioning
confidence: 99%
“…What constitutes moderate intake is historically and geographically diverse, and we have therefore covered the studies on biomarkers within the ranges reported as common social drinking, thereby excluding chronic abuse. Narrative reviews on alcohol intake biomarkers in relation to forensic and clinical studies have been published recently [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of low to moderate drinking beer on abdominal fat is a controversial issue, with conflicting evidence in the literature. The consumption of AB has been directly and proportionally correlated with the accumulation of visceral adipose mass, 33,34 but other studies describe the opposite or null effect. 51,52 In the present study, the dietary covariates were controlled and the participants were encouraged to drink beer at mealtimes.…”
Section: Discussionmentioning
confidence: 99%
“…Although consumption of beer has been associated with negative health effects in the general population, such as weight gain and visceral fat accumulation, 33,34 many studies have reported that moderate beer intake can have beneficial effects on the lipid profile, CV risk, and mortality, mainly attributable to the polyphenol content. [35][36][37] Nevertheless, few studies evaluating the relationship between beer and CVD have stratified their conclusions by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Taking a broader view, when pursuing further research on the effects of alcohol consumption, it is important to consider factors such as the quantity, frequency and context in which alcohol is consumed, as well as the specific population and clinical outcomes of interest [57]. For example, differences in the health effect of specific alcoholic beverages like red wine have been proposed [58], as have distinct patterns based upon frequency of intake and quantity consumed per drinking day [59]. Indeed, the 2021 ECS Guidelines specifically recommend a Mediterranean diet [56], including 'moderate' consumption of alcohol, and a distinct Mediterranean pattern has been described [60].…”
Section: Alcohol Drinking Pattern and Cardiovascular Healthmentioning
confidence: 99%